Analisis Akta Kelahiran Sebagai Jaminan Utang di Desa Sokogrenjeng Kenduruan Kabupaten Tuban Perspektif Hukum Islam - Kusmawati, Sri Ayu (Akademika, 2023)
Debt and receivables by guaranteeing birth certificates are now rife in various circles of rural communities. This often happens because there are many urgent needs that must be fulfilled. In order to further study debts and credit, this study aims to find out how the law guarantees birth certificates. This article includes field research studies using qualitative methods, namely researchers collecting data by observation, interviews with the parties concerned and documentation. Then the data obtained is analyzed by condensing data, presenting data, and drawing conclusions. The results of this study indicate that accounts payable using birth certificate guarantees that occurred in Sokogrenjeng village, Kenduruan District, Tuban Regency were carried out in the first way, cooperative employees came to residents' homes to provide loans, resulting in an agreement on debts and credits paid in installments 10 times installment or 3 months. If within 3 months you have not paid off, then you can apply for an extension. Second, the collateral practice does not meet the requirements, in which the deed is not worth rupiah/ cannot be traded. And in this debt there are additional payments that must be paid. According to the point of view of Islamic law in addressing birth certificates as collateral for debt, it can be concluded that debts with collateral for birth certificates that are carried out do not meet the collateral requirements, and the payment system also has additional payments that must be paid, so Islam considers this to be the same as usury. And usury is forbidden.